A Study on the Influence of Communication, Environment, Work, and Discipline Work on Employee Performance - Carlinda, Evelyn; Santosa, Agus Budi (Manunggal Halim Jaya, 2026)
This study aims to examine the influence of communication, work environment, and work discipline on team member performance at PT Zhi Sheng Indonesia in Semarang. The total population consisted of 100 employees, all of whom were included as respondents through saturated sampling. A survey method was employed, and multiple linear regression analysis was used to test the proposed hypotheses. Data were collected via questionnaires distributed to all employees. The results indicate that communication has a positive and significant effect on team member performance (β = 0.525; p = 0.000), followed by work discipline (β = 0.289; p = 0.000) and work environment (β = 0.166; p = 0.027). Simultaneously, these three variables significantly influence team member performance (F = 51.699; p = 0.000). The coefficient of determination (R² = 0.606) shows that 60.6% of the variance in employee performance is explained by communication, work environment, and work discipline. In comparison, the remaining 39.4% is influenced by other factors not examined in this study. These findings suggest that improving organizational communication, creating a supportive work environment, and strengthening work discipline can substantially enhance employee performance.